Changes and collapse in lacustrine system in Antarctic Peninsula ice-free area: Boeckella and Buenos Aires lakes - ROSEMARY VIEIRA; PRISCILA CARDOSO; KÁTIA K. DA ROSA; CARINA PETSCH; JUAN MANUEL LIRIO (Anais da Academia Brasileira de Ciências, 2024)
Abstract Some Antarctic ice-free areas have been affected by changes in lacustrine zones and permafrost thawing due to rising air temperatures over the last 60 years Temperature time-series were analyzed to understand the processes leading to the changes of Boeckella and Buenos Aires lakes, north Antarctic Peninsula. Statistical calculations were applied to average, maximum, and minimum temperatures, as well as to indexes such as Positive Degrees Day, Freezing/Thaw Day, and days with temperatures ≥ 0 °C and ≥ 10 °C. Changes in the region over recent decades were observed in mean and maximum temperatures and an increase in minimum temperature since the mid-1990s. In addition, the Normalized Difference Water Index was extracted from Landsat images from 2003, 2016, 2020, and 2021. These images were used to calculate changes in the areas of Boeckella and Buenos Aires lakes. These data revealed an 87% decrease in the area (m²) of Boeckella Lake and a 60% increase in Buenos Aires Lake´s area (m²). Concern has been raised about the modifying lake areas in the Antarctic Peninsula, where the collapse of Boeckella Lake could be the first case recorded in ice-free areas of Antarctica continent.